Sosialisasi Hukum Perlindungan Data Pribadi - Budi Handayani; Tuti Herningtyas; Haniyah Haniyah; Roidatus Shofiyah; Atmari Atmari (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The rapid development of digital technology has brought significant changes to society, particularly in the use of social media and internet-based services. However, the low level of public understanding regarding personal data protection has increased the risks of data misuse, online fraud, and privacy violations. This community service activity aims to improve public legal awareness regarding the importance of personal data protection in the digital era. The activity was conducted in Sidodadi Village on December 20, 2023, through socialization, legal counseling, interactive discussions, and question-and-answer sessions. The materials presented included the definition of personal data, forms of personal data misuse, legal protection based on Law Number 27 of 2022 concerning Personal Data Protection, and measures to maintain personal data security. The results of the activity showed an increase in public understanding of the importance of protecting personal data and using digital media more safely and wisely. In addition, this activity encouraged the emergence of new public awareness regarding the importance of protecting privacy rights in digital life. Therefore, legal socialization on personal data protection plays an important role in improving public legal literacy and digital literacy.